A survey into the respiratory effects of prolonged exposure to pulverised fuel ash. Issue 12 (December 1988) - Schilling, C J; Tams, I P; Schilling, R S; Nevitt, A; Rossiter, C E; Wilkinson, B
Abstract : Previous studies of respiratory disorders in workers exposed to pulverised fuel ash (PFA) have been confined to radiological effects that were found to be minimal. The present survey included 268 men (88% of the defined population) with a history of more than 10 years exposure to PFA in six power stations in the south east of England. Respiratory questionnaires with full occupational histories were obtained from all of these subjects, of whom 207 were actively employed and 61 had retired; 243 had lung function tests and 208 had chest x ray examinations. The men were grouped, using their occupational histories, into high, medium, and low exposure categories. Dust concentrations were obtained by personal sampling on a representative sample of men from the three exposure categories. Lung function tests showed that a modest effect on forced vital capacity, vital capacity, forced expiratory volume in one second, peak flow, and gas transfer (DCO) was associated with prolonged heavy exposure to PFA. The men with prolonged heavy exposure also showed higher prevalences of respiratory symptoms. No definite relation between exposure and x ray changes was established. The results of this cross sectional survey indicate that exposures to PFA should not exceed the limits recommended by the Health and Safety Executive for low toxicity dusts.